2017
DOI: 10.1039/c7gc02122d
|View full text |Cite
|
Sign up to set email alerts
|

New catalyst with multiple active sites for selective hydrogenolysis of cellulose to ethylene glycol

Abstract: Three different active sites were incorporated in 3-D silica matrix. One pot procedure was applied without using solvents or surfactants. The prepared material exhibited superior catalytic activity in the hydrogenolysis of cellulose to ethylene glycol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 37 publications
2
31
0
2
Order By: Relevance
“…With respect to the mass activity,t he activity variations among these five electrocatalysts were very similar to the variations of the specific activity.A so bserved, the mass activity of PtAg 1 was calculated to be 1728.3 mA mg À1 ,w hichw as 4.0, 1.8, 1.5, and 1.2 times higher than those of commercial Pt/C (431.2 mA mg À1 ), PtAg NCs (935.5 mA mg À1 ), PtAg 0.5 (1137.5 mA mg À1 ), and PtAg 1.5 (1382.1 mA mg À1 ), respectively,i ndicating its better electrocatalytic activity toward FAOR. [24,25] As illustrated in Figure S7 A, the PtAg 1 "nuts"d isplayed the slowest current decay over time and retainedt he highest mass activity among these catalysts.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…With respect to the mass activity,t he activity variations among these five electrocatalysts were very similar to the variations of the specific activity.A so bserved, the mass activity of PtAg 1 was calculated to be 1728.3 mA mg À1 ,w hichw as 4.0, 1.8, 1.5, and 1.2 times higher than those of commercial Pt/C (431.2 mA mg À1 ), PtAg NCs (935.5 mA mg À1 ), PtAg 0.5 (1137.5 mA mg À1 ), and PtAg 1.5 (1382.1 mA mg À1 ), respectively,i ndicating its better electrocatalytic activity toward FAOR. [24,25] As illustrated in Figure S7 A, the PtAg 1 "nuts"d isplayed the slowest current decay over time and retainedt he highest mass activity among these catalysts.…”
Section: Resultsmentioning
confidence: 96%
“…[22,23] As observed in Figure S11, PtAg 1 displayed the smallest diameter impedancea rc (DIA) among these electrocatalysts, indicating that the 3D PtAg 1 "nuts" possessed the smallest electron-transfer resistance and best electricalc onductivity,w hichw as consistentw ith their outstanding electrocatalytic performances.O ur efforts in this work clearly demonstrate that the as-obtained PtAg "nuts" showedg reatly enhanced electrocatalytic activity and reusability.T he enhanced performance of the uniform 3D PtAg "nuts"r eported herein is likely attributed to the combination of the structure and synergistic effect between Pt and Ag. [24,25]…”
Section: Resultsmentioning
confidence: 99%
“…Hamdy et al reported a novel 3Al-15W-3Ni catalyst prepared by one-pot hydrothermal sol-gel process for selective hydrogenolysis of cellulose into EG. The catalyst showed the multiple active sites and exhibited a high cellulose conversion (100%) and an excellent yield of EG with 76.0% at 229.85°C for 90 min under 4.0 MPa of H 2 pressure ( Table 3, entry 1) [273]. Ribeiro and coworkers synthesized a carbon nanotube-(CNT-) supported bimetallic 0.8%Ru-30%W/CNT catalyst prepared via a sequential incipient wetness impregnation method (first loaded with W and then with Ru component) for the hydrolytic hydrogenation of cellulose to EG, leading to 100% cellulose conversion and about 40% EG yield in aqueous solution at 205°C for 3 h of reaction under 5.0 MPa of H 2 pressure, which was demonstrated to be an improved catalytic performance compared with monometallic Ru/CNT or W/CNT catalyst under the same reaction conditions ( [288].…”
Section: Ethylene Glycol (Eg)mentioning
confidence: 99%
“…The synthesis was carried out by one-pot synthesis procedure based on sol-gel technique very similar to the synthesis method which was reported earlier by Hamdy and coworkers. [18][19][20] The activity of the prepared catalyst was investigated in the liquid phase, room temperature (298 K) and ambient pressure hydrogenation of cyclohexene. The stability and reusability were also investigated.…”
Section: Introductionmentioning
confidence: 99%